(untitled) (Alternate Horizons, 2021)
If we trace our cultural roots as Africans, we will realise that two major occupations have played big roles as primary sources of livelihood, particularly for rural community dwellers – subsistence agriculture and small-scale mining. In this paper, we will focus on the latter: its relevance, challenges, and the way forward.